The Performance Of Modified Internal Rate Of Return For Equity Investment Assessment: A Markov Chain Approach - M A Sarsour, Waseem (2021)
Recently, investors’ interest in the stock market and its performance has arisen. Investment and share prices are directly related, which makes the stock prices more volatile, and thus the investment is more likely to be of high risk. Research in capital budgeting has considered the application of the modified internal rate of return (MIRR) as an alternative technique to the traditional valuation methods such as the net present value (NPV) and the internal rate of return (IRR) to overcome certain limitations raised from these conventional methods, especially the problem of multiple IRR. However, literature on the MIRR method has some limitations including failing to take into account the share issuance function such as share split and consolidation as well as valuing the performance of an investment project in the long-run using the Markov chain based on the MIRR strategy could be problematic in case of insufficient sample size. Furthermore, the application of the Markov chain in valuing an investment project in the long-run was based on stock prices, NPV, and IRR. Combining these issues, this thesis aims to develop a long-term investment in terms of adjusting the MIRR strategy while considering the share issuance and reinvested dividends into account. Furthermore, this thesis implements Markov chain simulations to obtain the sufficient sample size required to assess the performance of an investment project using the Markov chain model based on the MIRR strategy. The proposed methods are illustrated using stock market data of public listed companies in the Malaysian Product Services and Industrial sector (MIPS) and compared to the stock prices method for robustness